The Three Estates Model: Represented and Satirised in Chaucer’s General Prologue to the Canterbury Tales - Doğan, Sadenur (Journal of History Culture and Art Research, 2013)
This paper presents an investigation of the 'Three Estates Model’ of the English medieval society in Chaucer’s General Prologue to the Canterbury Tales. Based upon the descriptions and illustrations of the characters, it aims to explore the hierarchal structure of the medieval society which is divided into three main groups or 'estates’: the ones who pray, the ones who rule and govern, and the ones who work. In the General Prologue, Chaucer gives a series of sketches of the characters that are the representatives of the three estates, and through these depictions he investigates the social characteristics and roles of the medieval people who are expected to speak and behave in accordance with what their social group requires. While presenting Three Estates Model, he employs the tradition of 'estates satire’ by criticising the social vices resulting from the corruption in this model. Through the characteristics and virtues of the 'Knight’, the 'Parson’, and the 'Plowman’, he demonstrates the perfect integration of the people who belong to chivalry, clergy and the commoners in the medieval English society. Also, by offering contrasting views to these positive traits in the portrayal of almost all of the other characters, as illustrated in the portrayal of the 'Monk’, the 'Reeve’, and the 'Wife of Bathe’ in this paper, he criticises the vices and sins (that are mainly resulted from the religious, financial and moral corruption) of the people belonging to the social classes of the Middle Ages.